2015
DOI: 10.1371/journal.pone.0143127
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Unplanned Intensive Care Unit Readmission Scores: A Prospective Cohort Study

Abstract: PurposeEarly discharge from the intensive care unit (ICU) may constitute a strategy of resource consumption optimization; however, unplanned readmission of hospitalized patients to an ICU is associated with a worse outcome. We aimed to compare the effectiveness of the Stability and Workload Index for Transfer score (SWIFT), Sequential Organ Failure Assessment score (SOFA) and simplified Therapeutic Intervention Scoring System (TISS-28) in predicting unplanned ICU readmission or unexpected death in the first 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 28 publications
4
39
0
6
Order By: Relevance
“…Points-based scores such as the Acute Physiology and Chronic Health (APACHE) score [21] and the Simplified Acute Physiology Score (SAPS) [22] are routinely used in ICUs to evaluate severity of illness and predict mortality risk; they may also be useful in predicting the risk of readmission [23]. However, a recent study comparing several scores used to predict the risk of readmission within 48 hours from discharge determined only moderate discrimination power (area under the receiver operating characteristic curve between 0.65 and 0.67) [24]. It is plausible that the application of novel machine learning algorithms to EMR data could lead to more accurate predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Points-based scores such as the Acute Physiology and Chronic Health (APACHE) score [21] and the Simplified Acute Physiology Score (SAPS) [22] are routinely used in ICUs to evaluate severity of illness and predict mortality risk; they may also be useful in predicting the risk of readmission [23]. However, a recent study comparing several scores used to predict the risk of readmission within 48 hours from discharge determined only moderate discrimination power (area under the receiver operating characteristic curve between 0.65 and 0.67) [24]. It is plausible that the application of novel machine learning algorithms to EMR data could lead to more accurate predictions.…”
Section: Introductionmentioning
confidence: 99%
“…It was also lower in comparison with the data from the Dutch National Intensive Care Evaluation (NICE) registry, in which a readmission rate of 8.2% was noted among 42,040 ICU admissions [15]. Additionally, Polish patients were generally hospitalized for much longer in the ICU in comparison with other countries [15,24,25]. These findings are not surprising.…”
Section: Discussionmentioning
confidence: 67%
“…Other studies have shown that determining the best timing for ICU discharge is usually based on subjective intuitions and that readmission prediction tools can help physicians in this endeavor, provided their performance and ease of adoption (5,6). As traditional scores based on logistic regression or Cox proportional hazards models such as the Stability and Workload Index for Transfer score (SWIFT) or the LACE index have failed to meet expectations (6)(7)(8)(9)(10), numerous prediction models using machine learning have been proposed in the recent past, several of which trained and evaluated on the Multiparameter Intelligent Monitoring in Intensive Care (MIMIC-II or MIMIC-III) open database (11)(12)(13)(14)(15). MIMIC-III is a large ICU EHR database widely accessible to researchers internationally under a data use agreement, allowing clinical studies to be reproduced and benchmarked (16,17).…”
Section: Introductionmentioning
confidence: 99%